Matrine Inhibits CNS Autoimmunity Through an IFN-β-Dependent Mechanism - Chu, Yao-Juan; Ma, Wen-Di; Thome, Rodolfo; Ping, Jie-Dan; Liu, Fang-Zhou; Wang, Meng-Ru; Zhang, Ming-Liang; Zhang, Guangxian; Zhu, Lin (Frontiers in Immunology, 2020)
Matrine (MAT), a quinolizidine alkaloid component derived from the root of Sophoraeflavescens, suppresses experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis (MS), by inducing the production of immunomodulatory molecules, e.g., IL-10. In an effort to find the upstream pathway(s) of the mechanism underlying these effects, we have tested certain upregulated immunomodulatory molecules. Among them, we found increased levels of IL-27 and IFN-β, one of the first-line MS therapies. Indeed, while the serum IFN-β production level was undetectable in saline-treated control EAE mice, it was increased after MAT treatment. Increased numbers of CD11b+IFN-β+ microglia/infiltrating macrophages were observed in the CNS of MATtreated mice. The key role of IFN-β induction in the suppressive effect of MAT on EAE was further verified by administration of IFN-β neutralizing antibody, which largely reversed the therapeutic effect of MAT. Further, we found that, while MAT treatment induced production of IL-27 and IL-10 by CNS microglia/macrophages, this effect was significantly reduced by IFN-β neutralizing antibody. Finally, the role of IFN-β in MAT-induced IL-27 and IL-10 production was further confirmed in human monocytes in vitro. Together, our study demonstrates that MAT exerts its therapeutic effect in EAE through an IFN-β/IL-27/IL-10 pathway, and is likely a novel, safe, low-cost, and effective therapy as an alternative to exogenous IFN-β for MS.